PENGARUH BATUBARA TERBAKAR DAN FAKTOR TERHADAP OUTPUT PLTU PADA PT. PEMBANGKIT JAWA BALI SERVICES KECAMATAN TIDORE UTARA - Husaen Salahu (DINTEK, 2022)
Steam Power Generators are energy-efficient kinetic energy from steam to generate electrical energy. This is a Steam Turbine device connected to a generator driven by kinetic power from hot / dry steam. The steam power plant uses a variety of fuels such as Gas, Oil, Coal, MFO (Marine Oil Fuels), Biomass and other combustible materials, to be borne at the Tidore Steam Power Center of Low Coal Fuel Type Rank Calory with grade Calory 4,500 -4,600 Kcal\ kg (Solid Fuel Classification According to WEC).Boiler is a generating device that serves to convert water into steam. Boiler consists of air-filled pipes. At the bottom there is a furnace that works to make heat. This heat will be used to evaporate the air in the pipes. And this steam will move the turbine. The steam produced by the boiler is Super Heat vapor with high pressure and temperature. Heat comes from hot air and fuel.Steam turbine serves to convert the heat energy contained in the vapor into mechanical energy in the form of rotation. Steam with high pressure and temperature flows through the Nozzle to speed up and precisely by pushing turbine blades mounted on the shaft. Turbo shaft moves to produce rotation (mechanical energy).Steam that enters the turbine or steam used to rotate the angle of the turbine depends on the amount of power to be generated. If desired large generated power will require steam Supply in large quantities, and vice versa if the power generated is small then steam Supply also a little. This Steam Supply arrangement is performed by a Control Valve that is set through the Central Control Room (CCR). To exhaust all components of this tool used coal as main molder with power and characteristic specifications produced as follows; loading coal as much as2724 tons, 231 tons tonnage, power generated every month 7801 mW, CF92%, CW 8%